Functional interaction between Lypd6 and nicotinic acetylcholine receptors. Issue 6 (15th August 2016) - Arvaniti, Maria; Jensen, Majbrit M.; Soni, Neeraj; Wang, Hong; Klein, Anders B.; Thiriet, Nathalie; Pinborg, Lars H.; Muldoon, Pretal P.; Wienecke, Jacob; Imad Damaj, M.; Kohlmeier, Kristi A.; Gondré‐Lewis, Marjorie C.; et al.
Abstract: Nicotinic acetylcholine receptors (nAChRs) affect multiple physiological functions in the brain and their functions are modulated by regulatory proteins of the Lynx family. Here, we report for the first time a direct interaction of the Lynx protein LY6/PLAUR domain‐containing 6 (Lypd6) with nAChRs in human brain extracts, identifying Lypd6 as a novel regulator of nAChR function. Using protein cross‐linking and affinity purification from human temporal cortical extracts, we demonstrate that Lypd6 is a synaptically enriched membrane‐bound protein that binds to multiple nAChR subtypes in the human brain. Additionally, soluble recombinant Lypd6 protein attenuates nicotine‐induced hippocampal inward currents in rat brain slices and decreases nicotine‐induced extracellular signal‐regulated kinase phosphorylation in PC12 cells, suggesting that binding of Lypd6 is sufficient to inhibit nAChR‐mediated intracellular signaling. We further show that perinatal nicotine exposure in rats (4 mg/kg/day through minipumps to dams from embryonic day 7 to post‐natal day 21) significantly increases Lypd6 protein levels in the hippocampus in adulthood, which did not occur after exposure to nicotine in adulthood only. Our findings suggest that Lypd6 is a versatile inhibitor of cholinergic signaling in the brain, and that Lypd6 is dysregulated by nicotine exposure during early development. Regulatory proteins of the Lynx family modulate the function of nicotinic receptors (nAChRs). We report for the first time that the Lynx protein Lypd6 binds to nAChRs in human brain extracts, and that recombinant Lypd6 decreases nicotine‐induced ERK phosphorylation and attenuates nicotine‐induced hippocampal inward currents. Our findings suggest that Lypd6 is a versatile inhibitor of cholinergic signaling in the brain. Abstract : Regulatory proteins of the Lynx family modulate the function of nicotinic receptors (nAChRs). We report for the first time that the Lynx protein Lypd6 binds to nAChRs in human brain extracts, and that recombinant Lypd6 decreases nicotine‐induced ERK phosphorylation and attenuates nicotine‐induced hippocampal inward currents. Our findings suggest that Lypd6 is a versatile inhibitor of cholinergic signaling in the brain.